Pengaruh Digital Skill, Pengalaman Magang, dan Future Time Perspective Terhadap Kesiapan Kerja Mahasiswa Sekolah Vokasi Universitas Negeri Padang - Dini Andriani; Tri Kurniawati (Universitas Negeri Padang, 2025)
The purpose of this study is to examine the influence of digital skills, internship experience, and future time perspective on the work readiness of vocational school students at Padang State University. This study is a causal study using a quantitative approach, which examines the relationship between variables and the object being studied in terms of cause and effect or problems in the study. The population consists of all active vocational school students at UNP who are in their 6th semester or higher, totaling 537 individuals. The sampling technique was based on specific criteria, namely students in their 6th semester or higher who had completed an internship. The sample size was calculated using the Slovin formula, resulting in 100 respondents, distributed proportionally across each program of study. A questionnaire was used to collect information, which was then evaluated using descriptive statistics and multiple linear regression. According to the data, digital skills, internship experience, and future time perspective have a significant impact on students' work readiness. With an adjusted R-square value of 0.282, these three variables explain 28.2% of vocational school students' work readiness at UNP, with the remaining percentage influenced by other factors not covered in this study.